2007
DOI: 10.1186/1472-6750-7-46
|View full text |Cite
|
Sign up to set email alerts
|

Construction of miniantibodies for the in vivo study of human autoimmune diseases in animal models

Abstract: Background: Phage display antibody libraries have been made from the lymphocytes of patients suffering from autoimmune diseases in which the antibodies are known to play a role in the pathogenesis or are important for the diagnosis of the disease. In the case of Celiac Disease, the immune response is directed against the autoantigen tissue transglutaminase. However, despite numerous studies, the role of these antibodies in the pathogenesis of this disease has not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…The extracellular portion of human ICOS and its mutated form carrying a phenylalanine to serine substitution at position 119 ( F119S ICOS-Fc) were cloned as fusion proteins to the human IgG1 Fc region, generating ICOSFc fusion protein, according to Di Niro et al (15). After transfection, CHO cells stably and highly expressing ICOS-Fc were established.…”
Section: Methodsmentioning
confidence: 99%
“…The extracellular portion of human ICOS and its mutated form carrying a phenylalanine to serine substitution at position 119 ( F119S ICOS-Fc) were cloned as fusion proteins to the human IgG1 Fc region, generating ICOSFc fusion protein, according to Di Niro et al (15). After transfection, CHO cells stably and highly expressing ICOS-Fc were established.…”
Section: Methodsmentioning
confidence: 99%
“…The single-chain fragment variables (scFvs) B2, anti-CD20, and anti-C5 18 (Adienne Pharma and Biotech) were subcloned into the pMB-SV5 19 vector containing the human IgG1 hinge-CH2-CH3 domains to obtain the human scFv-Fc format (MBB2, MBCD20, and MBC5). A CH2-deleted version of the scFv-Fc (DCH2) was generated as previously described 20 using the following primers: Hu_CH3_sense, 59ACGTGCTAGCCACACATGCCCA CCGTGCGGTGGAGGCGGTTCAGGCGGAGGTGGCTCTGGGCAGC CCCGAGAACCACAGG39;and Hu_CH3_anti, TGCTAAGCTTTTAAG TACTATCCAGGCCCAGCAGTGGGTTTGG.…”
Section: Cloning and Purification Of Recombinant Antibodiesmentioning
confidence: 99%
“…Adding mammalian antibody domains has been used to alter the characteristics of scFvs from various sources [36][37][38]. The present study has shown that the vectors and approaches developed by Greunke et al [24] to create larger bivalent molecules from monovalent chicken antibody fragments can be used for improving avian scFvs which under-perform in certain immunoassay applications.…”
Section: Discussionmentioning
confidence: 93%